Intra-abdominal pressure and rowing: the effects of inspiring versus expiring during the drive - Manning, T. S.; Plowman, S. A.; Drake, G.; Looney, M. A.; Ball, T. E. (The Journal of Sports Medicine and Physical Fitness, 2000)
BACKGROUND: The lumbar vertebrae of rowers are subjected to high levels of shear and compression at mid-drive, but intra-abdominal pressure (IAP) may partially neutralize these forces. IAP fluctuates with breathing. This study compared the IAP between inspiring during the drive and expiring during the drive. METHODS: Experimental design: ten volunteers performed one 5x2-minute repetition test while ispiring during the drive and one 5x2-minute repetition test while expiring during the drive on a rowing ergometer. The five work rates were: 100, 125, 150, 175 and 200 watts at 22, 24, 26, 28 and 30 strokes per minute, respectively. Measures: the movement of the body while rowing was analyzed using a position sensor, and IAP was measured using a pressure transducer catheter. RESULTS: A 2x5 repeated measures analysis of variance showed that there was a significant interaction for the dependent variable mid-drive IAP (p<0.05), with the mid-drive IAP increasing at a greater rate while expiring during the drive relative to inspiring during the drive. Across work rate, the mid-drive IAP and minimal IAP were significantly higher while expiring during the drive than inspiring during the drive (p<0.05). Across breathing pattern, the minimal IAP, maximal IAP, average change in IAP and mid-drive IAP increased significantly with work rate (p<0.05). CONCLUSIONS: The data show that expiring during the drive leads to a greater mid-drive IAP than inspiring during the drive.